2008
DOI: 10.1246/cl.2009.124
|View full text |Cite
|
Sign up to set email alerts
|

EPR Study of Rotational Diffusion in Viscous Ionic Liquids: Analysis by a Fractional Stokes–Einstein–Debye Law

Abstract: Rotational correlation time (τc) of nitroxide radical solute was determined in ionic liquids by utilizing CW EPR spectroscopy. The experimental values of τc determined in viscous ionic liquids disagree with the values calculated according to Stokes–Einstein–Debye (SED) equation. A fractional SED law was examined for these solute–solvent combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…Rotational (as well as translational) dynamics of dilute solutes have also been measured using ESR techniques on stable radical probes by several groups. Nearly all such studies have employed the TEMPO probe (2,2,6,6-tetramethylpiperidine-1-yloxyl) or its derivatives. For example, Strehmel and co-workers studied rotation of eight differently functionalized variants of TEMPO in a variety of ionic liquids .…”
Section: Introductionmentioning
confidence: 99%
“…Rotational (as well as translational) dynamics of dilute solutes have also been measured using ESR techniques on stable radical probes by several groups. Nearly all such studies have employed the TEMPO probe (2,2,6,6-tetramethylpiperidine-1-yloxyl) or its derivatives. For example, Strehmel and co-workers studied rotation of eight differently functionalized variants of TEMPO in a variety of ionic liquids .…”
Section: Introductionmentioning
confidence: 99%
“…The activation energy for the probe’s rotational tumbling in each solvent were reasonably close to those of the ILs viscous flow. 26 On the other side, Miyake et al 23 have observed that the rotational correlation time of proxyl radicals in [C 4 mim][BF 4 ] and [C 4 mim][PF 6 ] obeys a fractional SED law, which they compared with the rotation of TEMPO in supercooled liquids.…”
Section: Introductionmentioning
confidence: 99%
“…2 These characteristic features appeal to many researchers, interested in making new solvents with unique properties. [3][4][5][6][7][8][9][10][11][12][13] Various novel ILs that have paramagnetic and/or photochromic properties have been synthesized. [5][6][7][8][9] Recently, a new type of ILs having photochromic activity has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] Various novel ILs that have paramagnetic and/or photochromic properties have been synthesized. [5][6][7][8][9] Recently, a new type of ILs having photochromic activity has been developed. [10][11][12][13] These ILs contain a photofunctional substituent, such as a phenylazo group or a stilbene moiety, and following photoirradiation undergo a photochromic reaction, which leads to a change in the solvent properties.…”
Section: Introductionmentioning
confidence: 99%